National Institutes of Health Stroke Scale: comparison of original and modified versions for Singapore culture - Shu Han Lim; Tai Yan Guek; Fung Peng Woon; Deirdre Danyi Tay; Shu Swen Ho; Szu Chyi Ng; Deidre Anne De Silva (Singapore Medical Journal)
Introduction: The National Institutes of Health Stroke Scale (NIHSS), originally designed in the United States of America, contains items on dysphasia and dysarthria that are deemed culturally unsuitable for the Singapore context. We compared the error rates of dysphasia objects, dysphasia phrases and dysarthria words between the original and alternative items in a cohort of Singaporean subjects without dysphasia or dysarthria. Methods: In this prospective study, 140 English-speaking Singaporean subjects without impairments of dysphasia or dysarthria had an assessment of NIHSS items 9 and 10 using the original and alternative items. Paired analyses were conducted for comparison of error rates. Results: The error rates were high for four original dysphasia objects (Hammock: 62.9%, Cactus: 38.6%, Feather: 23.6%, Glove: 20.7%) and significantly lower for alternative items (Snail: 5%, Horse: 1.4%, Hanger: 1.4%, Car: 0%) (P < 0.001). For dysphasia phrases and dysarthria words, the error rates were low and there were no differences in error rates between the original and alternative items. Conclusion: There are cultural issues with several dysphasia objects in the original NIHSS as evidenced by the high error rates, which were lowered with more culturally suitable alternatives. This study formed a basis to derive a more suitable version of the NIHSS for English-speaking subjects in Singapore.